35.7k views
4 votes
Can someone help me with algebra 2 with an explanation?

Can someone help me with algebra 2 with an explanation?-example-1
User Prvit
by
5.5k points

1 Answer

1 vote

Answer: This took me a long time to type, hope you read it and find it helpful and easy to understand...

1.
x=1

2.
x=(3)/(2)

3.
x=1

4.
x=(6)/(5)

Explanation:

1.


(1)/(x)-(x-2)/(3x)=(4)/(3x)

To make it easier to add / subtract fractions, we are looking for common denominators. I can see that if I move the fraction on the left with a denominator 3x to the right, I'll be able to add two equations with like denominator.

Let's add
(x-2)/(3x)


(1)/(x)=(4)/(3x)+(x-2)/(3x)

Add the numerators and keep the same denominator.


(1)/(x)=(4+x-2)/(3x)


(1)/(x)=(2+x)/(3x)

To get rid of the denominator x on the left side, we can multiply by x.


(x)(1)/(x)=(2+x)/(3x)(x)


1=(2+x)/(3)

Now multiply by 3.


(3)1=(2+x)/(3)(3)


3=2+x

Subtract 2.


3-2=x\\1=x

The value of x is 1.

Proof.


(1)/(x)-(x-2)/(3x)=(4)/(3x)


(1)/(1)-(1-2)/(3(1))=(4)/(3(1))


1-(-1)/(3)=(4)/(3)


1+(1)/(3)=(4)/(3)


(1*3+1)/(3) =(4)/(3)\\(4)/(3)=(4)/(3)

I can't show the proof to the following problems because I have a 5000 character limit.

-----------------------------------------------------------------------------------------

2.


(5x-5)/(x^2-4x) -(5)/(x^2-4x)=(1)/(x)

Again, we have like denominators, therefore, we can simply subtract the numerators and keep the same denominator.


(5x-5-5)/(x^2-4x)=(1)/(x)


(5x-10)/(x^2-4x)=(1)/(x)

Again, we can multiply by x to get rid of the x in the denominator.


(x)(5x-10)/(x^2-4x)=(1)/(x)(x)

Do not distribute the x in the numerator yet because we're gonna eliminate it later.


((x)(5x-10))/(x^2-4x)=1

Factor the denominator.


((x)(5x-10))/((x)(x-4))=1

Simplify x's.


(5x-10)/(x-4) =1

Multiply by x-4 to get rid of the denominator.


(x-4)(5x-10)/(x-4) =1(x-4)


5x-10=x-4

Add 10


5x=x-4+10

Subtract x


5x-x=-4+10

Combine like terms;


4x=6

Divide by 4.


(4x)/(4)=(6)/(4)


x=(6)/(4)

Simplify by 2.

6/2 = 3

4/2 = 2


x=(3)/(2)

-----------------------------------------------------------------------

3.


(x^2-7x+10)/(x)+(1)/(x)=x+4

Same denominator, add numerators.


(x^2-7x+10+1)/(x)=x+4


(x^2-7x+11)/(x)=x+4

Multiply by x to get rid of the x.


(x)(x^2-7x+11)/(x)=(x+4)(x)


x^2-7x+11=x^2+4x

Subtract
-x^2-4x


x^2-7x+11-x^2-4x=0

Combine like terms;


-11x+11=0

Subtract 11.


-11x=-11

Divide by -11


x=(-11)/(-11) \\x=1

-------------------------------------------------------------------------

4.


(x^2+7x+10)/(5x-30)+(x)/(x-6)=(x^2-13x+40)/(5x-30)

It's easier if you move the operation with denominator x+6 to the right side with negative sign and bring the operation on the right side to the left side with negative sign as well.


(x^2+7x+10)/(5x-30)-(x^2-13x+40)/(5x-30)=-(x)/(x-6)

Now, since we have the same denominators, we can simply subtract numerators.


(x^2+7x+10-(x^2-13x+40))/(5x-30) =-(x)/(x-6)

Distribute the negative sign.


(x^2+7x+10-x^2+13x-40)/(5x-30) =-(x)/(x-6)

Combine like terms;


(20x-30)/(5x-30)=-(x)/(x-6)

Factor.

I can see that I can factor a 5 on both numerator and numerator. This will allow me to simplify them.


((5)(4x-6))/((5)(x-6)) =-(x)/(x-6)

Simplify.


(4x-6)/(x-6)=-(x)/(x-6)

Multiply by x-6


(x-6)(4x-6)/(x-6)=-(x)/(x-6)(x-6)

This will simplify the denominators.


4x-6=-x

Add x and 6.


4x+x=6\\

Combine like terms;


5x=6

Divide by 5.


x=(6)/(5)

User Sander Smits
by
5.0k points